0D Perovskites: Unique Properties, Synthesis, and Their Applications. Issue 24 (24th October 2021) - Sun, Siqi; Lu, Min; Gao, Xupeng; Shi, Zhifeng; Bai, Xue; Yu, William W.; Zhang, Yu
Abstract: 0D perovskites have gained much attention in recent years due to their fascinating properties derived from their peculiar structure with isolated metal halide octahedra or metal halide clusters. However, the systematic discussion on the crystal and electronic structure of 0D perovskites to further understand their photophysical characteristics and the comprehensive overview of 0D perovskites for their further applications are still lacking. In this review, the unique crystal and electronic structure of 0D perovskites and their diverse properties are comprehensively analyzed, including large bandgaps, high exciton binding energy, and largely Stokes‐shifted broadband emissions from self‐trapped excitons. Furthermore, the photoluminescence regulation are discussed. Then, the various synthetic methods for 0D perovskite single crystals, nanocrystals, and thin films are comprehensively summarized. Finally, the emerging applications of 0D perovskites to light‐emitting diodes, solar cells, detectors, and some others are illustrated, and the outlook on future research in the field is also provided. Abstract : The unique crystal and electronic structure of 0D perovskites and their photoluminescence mechanism are comprehensively analyzed in this review. The different synthetic methods for 0D perovskite crystals and thin films, and their diverse applications are also discussed. In addition, the outlook on future research in the field is provided.